2018
DOI: 10.7567/jjap.57.103002
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism of Cu-doped anatase TiO2: the first-principles calculation study

Abstract: The electronic structures and magnetic properties of Cu-doped anatase TiO2 have been investigated by first-principles calculations based on the density functional theory (DFT). Calculation results indicated that one Cu-substituted Ti (Cu@Ti) defect can introduce a total magnetic moment of 1 μB, which mainly distributed on the doped Cu atom and six neighboring oxygen atoms. In accordance with the group theory, the fivefold Cu-3d energy level splits into one threefold t2g orbital and one twofold eg orbital under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…We use SGGA + U and choose 10 × 10 × 5 k-point meshes in the geometry optimizations. We set U = 3 eV cause previous studies have shown that is sufficient for transition metal-doped anatase [44][45][46]. The force is less than 0.02 e V/Å −1 on each atom, and the calculation will be terminated till the energy is less than 10 -5 eV.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…We use SGGA + U and choose 10 × 10 × 5 k-point meshes in the geometry optimizations. We set U = 3 eV cause previous studies have shown that is sufficient for transition metal-doped anatase [44][45][46]. The force is less than 0.02 e V/Å −1 on each atom, and the calculation will be terminated till the energy is less than 10 -5 eV.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…[ 20 ] Previous studies have proposed that the ferromagnetism in Cu‐doped TiO2$\left(\text{TiO}\right)_{2}$ originates from the double‐exchange interaction between Cu ions. [ 21 ]…”
Section: Resultsmentioning
confidence: 99%
“…[20] Previous studies have proposed that the ferromagnetism in Cu-doped TiO 2 originates from the double-exchange interaction between Cu ions. [21] The exchange interactions between Cu ions are restricted by the radius of the Cu 3d electrons and diminish as the distance between two Cu ions increases. [19] We investigated the exchange interactions between Cu ions at various distances by computing the energy differences in different supercells, as shown in Figure S2, Supporting Information.…”
Section: Magnetic Interaction In the Cu-doped Tiomentioning
confidence: 99%
See 2 more Smart Citations